Sub-system level numerical simulation investigation of the S-shaped inlet and the rear subsonic fan-stage. (June 2018) - Lei, Liu; Hua-Chen, Pan; Jie-Gang, Mu; Fu, Chen; Yan-Ping, Song; Xiao-Qing, Tian
For investigating the evolution process of a half flush-mounted air intake exit distortion in the downstream flow field and also its effects on the fan-stage performance, sub-system level numerical simulation of the whole structure of the air intake and the fan-stage was carried out. Considering large boundary layer ingestion, a scheme that bleeding air from stator for blowing control in the front air intake was also proceeded. At the same time, both the single fan-stage with uniform air admission and the single airintake without fan-stage are researched for comparison. The results show that giving a real exit boundary or not has significant impact on the airintake numerical simulation results, especially to the circumferential total pressure distortion and the swirl distortion at the airintake exit. Due to large boundary layer ingesting, the aerodynamic performance of the fan-stage declines a lot. As comparing with the homogeneous air admission condition, the maximum isentropic efficiency and the choked mass flow of the fan-stage decrease about 4.17% and 1.31%, respectively. After bleeding air from the stator, the overall performance of the fan-stage changes significantly. It improves a lot when the fan-stage works between the maximum efficiency point and the stall margin while decreases under other conditions. The distorted low energy fluid from upstream always covers several passages as it goes through the fan-stage. And in the meanwhile, severe flow separation appears at suction side of stator blades, no matter the bleed air flow control executed or not. Impact of the design of the bleed air pipe on the control effect is large, and the best bleed air pipe for flow control is needed to further research in the future.